Germination and morphology of seeds and seedlings of Parkia gigantocarpa fabaceae: Mimosoidae - Ribeiro, Jonathan Wesley Ferreira [UNESP]; de Oliveira, Ademir Kleber Morbeck; Rodrigues, Adriana Paula D'Agostini Contreiras; Rondon, Eliazel Vieira (Universidade Federal do Paraná, 2015)
Parkia gigantocarpa is a valuable timber tree, and due to its rapid growth and great survival can be used to enrich forest clearings. The aims of this study was describe main morphological characters of seeds and seedlings, and to evaluate germination and initial growth of the species at six temperatures. The seed shape varies from elliptical, oblong or ovoid with bone consistency surface, smooth, glossy black color and presence of pleurogram. Average dimensions were 21.25 mm (length), 10.43 mm (width), and 6.15 mm (thickness). The embryo type is linear axial, with fleshy cotyledons, convex planes and dominant. The germination is epigeous phanerocotyledonary with fleshy cotyledons, and occurs between the second and fifth days after sowing. The fully developed seedling stage was reached on the fifteenth day after sowing. Temperatures of 30 and 35 C provided higher germination rates in less time and with higher root biomass allocation.
Keywords: Amazon; Biometrics; Fava-atanã; Forest seeds; Germination temperature